Interprofessional collaboration and lecturers´ working life periods: Evaluation of the outcomes and pilot study of Competent Teacher Scale (CTS) - Riitta-Liisa Lakanmaa; Elina Kontio (Finnish Social and Health Informatics Association, 2016)
Nowadays healthcare and engineering education should respond to the demands of the continuously changing working life. The aim of this study was to describe the outcome of the eHealth related working life period to the competence of lecturers (N=28) of vocational education and to pilot test the developed Competent Teacher Scale (CTS). The lecturers self-assessed as best competence domain "Practice orientation", the second best competence they assessed "Interprofessional collaboration" and as third competence domain they assessed "Development of education". The lecturers self-assessed "eHealth" as the worst competence domain in point of the content of competence according to InnoHealth project. The first version of CTS worked well as internal assessment purposes in the project and should be further developed and tested in future.